The Literary Semiotic Studies in the Novel Ringin Kurung - Winarsih Winarsih; Endang Winasih; Cahya Indah Apriliyana (Abjad Journal of Humanities & Education, 2023)
This study aims to analyze and describe the semiotic system that refers to the elements of icons, indexes, and symbols in Pak Mett's novel Ringin Kurung. The novel is a Javanese language novel that has a romance genre. It is a novel that has prominent elements, both intrinsic and extrinsic. The novel is interesting to study because it has elements of signs and implied meanings. The problem of understanding meaning in a complex literary work full of language games and elements of the author's creativity is not easy. So, this kind of study is needed. Analyzing the novel is a novelty that has never been done before. This study used a descriptive qualitative method. To be able to describe and analyze text in the form of words or sentences. The qualitative in question places more emphasis on the element of meaning. The approach used is Charles Sanders Pierce's semiotic theory. Literary semiotic theory interprets signs through icons, indexes, and signs. Sources of data from the novel Ringin Kurung by Pak Mett, journals, and books as references that support studies in research. The data collection technique is observation, namely observing and recording, followed by searching, reading, understanding, and concluding. The data analysis is thorough. From this research, it was found that there are signs in the form of icons, indexes, and symbols in Pak Mett's novel Ringin Kurung. There are icons, including plants (banyan trees), food (tempe and arem-arem), and places (square and hospital). The index is in the form of subordinate behaviour to the employer, polite behaviour index, firefly index, sultry index, and strategic index. As well as symbols, namely Ringin Kurung, vehicles (cars), goods (reclining chairs), blushing, fast breathing, and katresnan.